Türkiye'de eczacılık doktoralarının başlaması ve 1983 öncesinde İstanbul Üniversitesi'nde yapılan eczacılık doktoraları - (:unkn) unknown (My University, 2011)
Türkiye'de eczacılık eğitimi, resmi olarak ilk kez 1839'da Mekteb-i Tıbbiye-i Adliye-i Şâhâne bünyesinde açılan 'Eczacı Sınıfı' ile başladı. Daha sonra, 1909 yılında Darülfünun Tıp Fakültesi içinde bir Eczacı Okulu açıldı ve eczacılık eğitimi, okulun Fen Fakültesi'ne bağlı olduğu 1933-44 dönemi hariç Tıp Fakültesi içinde verildi. 1960 yılında Ankara Üniversitesi Eczacılık Fakültesi'nin açılmasının ardından, eczacılık eğitimi yalnızca eczacı yetiştiren fakültelerde verildi. Türkiye'de doktora çalışmaları 1930'lu yıllarda başladı. Türkiye'de eczacılık alanında ilk doktora çalışması 1942 tarihinde Hayriye Amal tarafından İstanbul Üniversitesi'nde yapılmıştır. 1983 yılında sonra, lisansüstü eczacılık eğitimi Sağlık Bilimleri Enstitüleri tarafından organize edilmiştir. 1942 - 1983 yılları arasında eczacılık alanında toplam 139 doktora çalışması tamamlanmıştır. Bunun yanında yabancı ülkelerde yapılmış çok sayıda doktora da mevcuttur. Bu çalışmada, Sağlık Bilimleri Enstitülerinin kurulmasından önce, eczacılık alanında yapılan doktora çalışmalan üzerinde durulmuştur. Bu dönemde doktora yapan akademisyenler bugün eczacılık fakültelerinde lisans ve lisansüstü eğitim veren ve eczacılık alanında bilimsel çalışmalar yapan akademik kadronun çekirdeğini oluşturmaktadır. Bu çalışma, eczacılık eğitiminin ve araştırmalarının günümüze kadar geçirdiği değişimin anlaşılmasına katkıda bulunmayı amaçlamaktadır.

The pharmaceutical education in Turkey started with the creation in 1839 of a 'Class of Pharmacy' within the Imperial School of Medicine (Mekteb-i Tıbbiye-i Adliye-i Şâhâne). Later on, a School of Pharmacy was established in 1909 was affiliated to the Faculty of Medicine, except for the period 1933-44 when it was attached to the Faculty of Science in Istanbul. The first faculty of pharmacy was founded in 1960 within the Ankara University, and since then the pharmaceutical education has been continued in the numerous faculties of pharmacy in Turkish universities. Awarding a doctorate degree began in Turkey in the 1930s. The first doctoral thesis in pharmaceutical sciences was prepared by Hayriye Amâl in 1942 in Istanbul University. Between 1944 and 1960, postgraduate education was under the administration of the faculties of medicine and sciences. In 1983, the Institutes for Health Sciences founded in Turkish Universities undertookthe management of postgraduate education in health sciences, includifig the pharmaceutical sciences. 139 theses pertaining to pharmaceutical sciences were defended between 1942 and 1983. Additionally, many candidates havp prepared and received their doctoral theses abroad. The present study focuses on the doctoral dissertations completed in pharmaeutical sciences prior to the foundation of the Institutes for Health Sciences in 1983. Scholars who have obtained their doctoral degree before 1983 constituted the very core of the academic staff in charge of the graduate and postgraduate programs in pharmaceutical education and responsible for carrying out the reseach in pharmaceutical sciences. The present study, aims to contribute to the understanding of the evolution of pharmaceutical education and research up to the present day.
The doctoral dissertations in pharmaceutical sciences in Istanbul University prior to 1983
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Müzik